Answer :
Answer:
The answer for this question is : [tex](x+4)(3x+1)(3x-1)[/tex]
Step-by-step explanation:
[tex]=9x^3+36x^2-x-4\\=(x+4)(3x+1)(3x-1)[/tex]
Answer:
Your answer is (3x + 1)(3x − 1)(x + 4) or in letter terms, B on your exam!
Step-by-step explanation:
Let's solve this together!
First we use the rational roots theorem to find a root.
The general formula for a third-degree polynomial is f(x) = ax³ + bx² + cx + 3
And our polynomial is ƒ(x) = 9x³ + 36x² − x − 4
Time to define our variables!: a = 9; d = -4
According to the Rational Roots Theorem, the possible rational roots are the factors of d divided by the factors of a.
Factors of d = ±1, ±2, ±4,
Factors of a = ±1, ±3, ±9
So there are 20 possible roots ranging from x = -4 to x = 4 that we can evaluate.
First we're going to give x = -4 a shot.
f(-4) = 9(-4)³ + 36(-4)² − (-4) − 4 = 9(-64) + 36(16) + 4 - 4 = -576 + 576 =0
It worked! x = -4 is a root, and (x+ 4) is a factor of the polynomial
After we use synthetic division we must write the complete factorization
ƒ(x) = (x + 4)(3x + 1)(3x - 1)
There! That would be your answer, young mind!
Hope this helped ya! \(*^▽^*)/ Sincerely, Kelsey from Brainly
~ #LearnWithBrainly ~